Public Services Under Private Management - Maíra Coube; Luiz Felipe Fontes; Rudi Rocha (The Quarterly Journal of Economics, 2026)
Abstract Theory predicts that outsourcing public services to the private sector can reduce costs and improve efficiency but can also induce cost-cutting and compromise quality. We assess the Brazilian Organizações Sociais de Saude model (OSS), which outsources management of public hospital services to the private sector while the state remains the residual claimant. We show that this enhances hospital production and operational efficiency without adverse effects on hospital quality and equity. Increased inpatient production addresses previously unmet demand, expanding local access to hospital care and reducing population mortality. Performance gains arise from improved operational efficiency achieved through increased hospital management capacity. This facilitates staffing adjustments, favoring higher-skilled personnel, dismissing lower-productivity staff, and adopting flexible, performance-tied employment contracts. Effects are larger among private organizations with more management experience, underscoring returns to managerial capacity. Our findings show that incentive-ownership structures can address the quantity-quality trade-off in public service delivery, even when contracts are incomplete and quality is hard to measure.